A REVIEW OF THE LITERATURE ON THE DEVELOPMENT OF ENGLISH INSTRUCTORS' TPACK IN INDONESIA - Hasibuan, Susi Su'aidah; Dewi, Utami; Daulay, Sholihatul Hamidah (Jurnal As-Salam, 2022)
In this twenty-first century, It is essential that English instructors continually build their TPACK to improve language teaching and learning. Research on the development of TPACK in Indonesia has been in great demand by academics and researchers. Therefore, the purpose of this study is to give a thorough synthesis of the reported outcomes of Indonesian English instructors' TPACK development. The evolution of TPACK for English teachers is examined in this literature review, which is structured circa five disparate research techniques (self-report measures, open-ended questionnaires, performance assessments, interviews, and observations). In order to do this, a search in 2011–2021, Education Research Information Center (ERIC), Taylor and Francis, and Library Genesis databases was carried out. Eight studies were deemed appropriate for analysis in the current study after criteria were applied to publications retrieved from the databases. There was a three-level analysis done. The first was a study-level analysis focused on each study's overall features. The second method analysis concentrated on the research tools and target audience. The final one provided a summary of the study findings through the literature to show the outcome of Indonesian instructors' TPACK development. The results of this present study gave an overview of the research techniques and the result on TPACK development. Additionally, this study also demonstrated an upsurge in publications regarding TPACK development among English instructors in Indonesia.